The Power Enhancement of a Mini-Gas Turbine by Adding Ethanol to the Compressor Inlet Air - Al-Saraf, Abdul Satar J.; Al-Jumaily, Suhad A. R. (Al-Khwarizmi Engineering Journal, 2013)
An experimental study is conducted on the utilization of the inlet ethanol injection technique in order to evaluate its impact on the performance of a two-shaft T200D mini-gas turbine engine. The maximum degradation recorded in power output was 32.8% at the climate temperature of 45oC. Nevertheless, at that temperature, adding ethanol with Eth/LPG ratio of 20% by volume brought an enhancement in power output of 19.2% compared to normal LPG run. SFC of the dual-fuel engine ranked a level of 22% higher than that with pure LPG consumption. The overall efficiency suffered a maximum reduction of 14.4% with Eth/LPG fuel ratio of 20%, but when the loading was raised beyond 70% of the engine full load; the efficiency of dual-fuel engine excelled the normal LPG engine by 3.1% at the corresponding Eth/LPG ratio maintaining a power turbine speed of 12000 rpm.